Hybrid exponentially weighted moving average control chart for mean by using different ranked set sampling schemes - Noor ul amin, Muhammad; Shabbir, Navara; Khan, Nasrullah; Riaz, Afshan (Kuwait Journal of Science, 2020)
In this paper different schemes of ranked set sampling (RSS) are used to design a new hybrid exponentially weighted moving average (HEWMA) control chart having more sensitivity to small and moderate shifts.The suggested control chart dominates classical exponentially weighted moving average (EWMA) control chart, EWMA based on RSS and HEWMA control chart using simple random sampling (SRS). The ARLs and SDRLs based on Monte Carlo simulations are used as an evaluation measure for the sensitivity of proposed control chart which shows that the HEWMA using RSS schemes significantly increases the performance of control chart. An example containing real data is also given to further explain the application.